Academic integrity and academic culture - Chornobai, Vira; Чорнобай, Віра Георгіївна (Дніпровський державний аграрно-економічний університет, 2024)
There are two ways of forming and observing the “norm” regarding the issue of negligence in Ukrainian education – conscious and unconscious behavior. Methods of preventing academic dishonesty are most common in the practice of Western educational institutions. Western experience of punishment for dishonesty: from retaking the exam, relistening to the course and rewriting the work before expulsion from the university. Існує два шляхи формування та дотримання «норми» щодо проблеми недбалості в українській освіті – свідома та несвідома поведінка. Методи попередження академічної нечесності найбільш поширені в практиці західних навчальних закладів. Західний досвід покарання за нечесність: від перездачі іспиту, переслуховування курсу та переписування роботи до виключення з університету.
Академічна доброчесність та академічна культура
Keywords: academic integrity; академічна доброчесність; academic culture; академічна культура; professional education; професійна освіта; academic dishonesty; академічна нечесність; competitive; конкурентоспроможність